Non-profit Governance: Twelve Frameworks for Organisations and Research - Turpin, Aaron (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale, 2025)
The following article is a book review of Non-profit Governance: Twelve Frameworks for Organizations and Research. It begins with an overview of main concepts and overarching themes in the book and summarizes chapter-specific material. Key points, including resource dependencies, external pressures, and and future directions for research and practice, are outlined. Finally, a discussion on how the book frames the role of nonprofits and community and promotes interdisciplinary governance work is provided, and concluding remarks complete the review.